Effects of Exercise Preconditioning Mediating Oxidative Stress to Regulate PI3K/Akt and Nrf2/HO-1 Pathways to Alleviate Cognitive and Learning Disorders in Rats - KONG Haijun; LI Xinlong; WANG Fenghua; CHEN Xiaoan (康复学报)
ObjectiveTo explore the basic mechanism of exercise preconditioning regulating PI3K/Akt and Nrf2/HO-1 signa-ling pathways and oxidative stress to alleviate cognitive and learning disabilities in rats with hypoxic exposure.MethodsA total of sixty 6-week-old SPF male SD rats were divided into control group, exercise group, exposure group and exercise + exposure group according to random number table method, with 15 rats in each group. The control and exposure groups received no exercise preconditioning intervention, while the exercise and exercise + exposure groups received exercise preconditioning intervention (treadmill training, twice a day, 6 days a week, a total of 4 weeks of training). The day after exercise preconditioning, rats in the exposure and exercise + exposure groups received hypoxia exposure for 7 days. After 7 days of hypoxia exposure, the cognition and learning ability of rats were evaluated by open field test and Morris water maze test. SOD and GSH activities, MDA content and IL-1β, IL-6 and TNF-α levels in serum of rats were detected by enzyme-linked immunosorbent assay (ELISA). The changes of Nissl corpuscles in CA1 region of hippocampus were observed by Nissl staining. mRNA expression levels of PI3K, Nox1, Duox2 and Akt were detected by RT-PCR. The relative expression levels of Nox1, Duox2, GCLM and PI3K/Akt and Nrf2/HO-1 pathway proteins in hippocampus were detected by Western blot.ResultsCompared with the control group and the exercise group, the 3 d escape latency of the exposed group increased (P<0.05). The times of the platform crossings and the residence time in platform significantly decreased (P<0.05). Serum MDA content, IL-1β, IL-6 and TNF-α levels significantly increased (P<0.05), while SOD and GSH activities signi-ficantly decreased (P<0.05). The number of Nissl bodies in CA1 region decreased (P<0.05). The mRNA expression levels of PI3K, Nox1 and Duox2 increased (P<0.05), while the mRNA expression level of Akt decreased (P<0.05). The relative expressions of Nox1, Duox2 and GCLM proteins in hippocampus significantly increased (P<0.05), while the ratios of p-PI3K/PI3K, p-Akt/Akt, p-GSK-3β/GSK-3β and the relative expressions of Nrf2 and HO-1 proteins significantly decreased (P<0.05). Compared with the exposure group, the movement time in the central area, the 3 d escape latency decreased (P<0.05), the number of platform crossings and the platform quadrant residence time increased (P<0.05) in the exercise + exposure group. Serum MDA content, IL-1β, IL-6 and TNF-α levels significantly decreased (P<0.05), while SOD and GSH activities significantly increased (P<0.05). The damage of neurons in CA1 region was reduced and the number of Nissl corpuscles increased. The mRNA expression levels of PI3K, Nox1 and Duox2 in hippocampus tissues decreased (P<0.05), while the mRNA expression level of Akt increased (P<0.05). The relative expression levels of Nox1, Duox2 and GCLM proteins in hippocampus significantly decreased (P<0.05), while the ratio of p-PI3K/PI3K, p-Akt/Akt, p-GSK-3β/GSK-3β and the relative expression levels of Nrf2 and HO-1 proteins significantly increased (P<0.05).ConclusionExercise preconditioning may be involved in the regulation of oxidative stress in brain tissue by activating PI3K/Akt and Nrf2/HO-1 signaling pathways, and thereby improves the neurobehavioral functions of hypoxia exposed rats.